2022
DOI: 10.1111/hel.12897
|View full text |Cite
|
Sign up to set email alerts
|

Persistent advanced periductal fibrosis is associated with cagA‐positive Helicobacter pylori infection in post‐praziquantel treatment of opisthorchiasis

Abstract: Background Liver fluke infection caused by Opisthorchis viverrini is associated with several hepatobiliary diseases including advanced periductal fibrosis (APF) and cholangiocarcinoma. Recently, we demonstrated a persistent APF in over one‐third of opisthorchiasis patients after worm removal by praziquantel (PZQ) treatment. However, the underlying mechanism(s) of this phenomena is unclear. Given a co‐infection with Helicobacter pylori (H. pylori) especially cagA‐positive strain enhances APF, we hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The interrelationship among several factors might be theoretically possible and it can be the main pathobiological process for cholangiocarcinoma development. 4 The current study by Phung et al 1 can still not rule out the effect of other confounding factors.…”
mentioning
confidence: 59%
“…The interrelationship among several factors might be theoretically possible and it can be the main pathobiological process for cholangiocarcinoma development. 4 The current study by Phung et al 1 can still not rule out the effect of other confounding factors.…”
mentioning
confidence: 59%
“…There is now a great deal of evidence to show that Ov may serve as a reservoir of H. pylori, a Gram-negative bacterium, resulting in coinfection with the two pathogens in endemic areas [19]. Furthermore, a long-term follow-up study following praziquantel treatment to clear Ov infection has shown that those with relapsed or persistent APF have a statistically-significant higher incidence of infection with cagA-positive H. pylori [20]. However, the mechanism by which cagA-positive H. pylori drives APF is still undefined.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature proposes that a carcinogenic bacterium, Helicobacter pylori ( H. pylori ), also contributes to the development of cholangiocarcinoma by enhancing the severity of hepatobiliary abnormalities [ 67 ]. A study by Hang et al found that even after completion of therapy with praziquantel, patients with co-infection by H. pylori , especially cagA-positive strain, continued to have persistent APF [ 68 ]. Hence, this suggests the need for concurrent H. pylori treatment for better outcomes.…”
Section: Treatmentmentioning
confidence: 99%